Prospects for using X-ray free-electron lasers to investigate shock-compressed matter - Nagler, B; Higginbotham, A; Kimminau, G; Murphy, W; Whitcher, T; Wark, J; Hawreliak, J; Kalantar, D; Lee, R; Lorenzana, H; Remington, B; Larsson, J; et al. (2007)
Within the next few years hard X-ray Free Electron Lasers will come on line. Such systems will have spectral brightnesses ten orders of magnitude greater than any extant synchrotron, with pulse lengths as short as a few femtoseconds. It is anticipated that large-scale optical lasers capable of shock-compressing matter to multi-megabar pressures will be sited alongside the X-ray source. We discuss how such systems can further our knowledge of shocked and isochorically heated matter, in particular investigating the potential to perform poly crystalline diffraction and the creation of warm dense matter. © 2007 American Institute of Physics.